Answer:
![\displaystyle \textcolor{black}{4.}\:[-3, -5]](https://img.qammunity.org/2023/formulas/mathematics/college/2nq41pzvyb1wu84xkktmo5gkeo2vbehtod.png)
![\displaystyle \textcolor{black}{3.}\:[8, -1]](https://img.qammunity.org/2023/formulas/mathematics/college/w1yda2r8mthuvstookvp69jv3v55x0mpcs.png)
![\displaystyle \textcolor{black}{2.}\:[4, -7]](https://img.qammunity.org/2023/formulas/mathematics/college/b8bv6lcu9bhikwyav1qhqpe6scrhlclqdw.png)
![\displaystyle \textcolor{black}{1.}\:[3, -2]](https://img.qammunity.org/2023/formulas/mathematics/college/d7sc9phefrw3jsoo8quv7ybgwjloh4ekng.png)
Explanation:
When using the Elimination method, you eradicate one pair of variables so they are set to zero. It does not matter which pair is selected:
![\displaystyle \left \{ {{2x - 3y = 9} \atop {-5x - 3y = 30}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/7e1ncnkganm6gpi6j60zbrspxry9ulc1qx.png)
{2x - 3y = 9
{⅖[−5x - 3y = 30]
![\displaystyle \left \{ {{2x - 3y = 9} \atop {-2x - 1(1)/(5)y = 12}} \right. \\ \\ (-4(1)/(5)y)/(-4(1)/(5)) = (21)/(-4(1)/(5)) \\ \\ \boxed{y = -5, x = -3}](https://img.qammunity.org/2023/formulas/mathematics/college/7efm0repgedikmdi0jxh8i009f9wmvk6z9.png)
------------------------------------------------------------------------------------------
![\displaystyle \left \{ {{x - 2y = 10} \atop {x + 3y = 5}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/vmd4dynorv9vmzfdvngtlfo34ojxph8xkz.png)
{x - 2y = 10
{⅔[x + 3y = 5]
![\displaystyle \left \{ {{x - 2y = 10} \atop {(2)/(3)x + 2y = 3(1)/(3)}} \right. \\ \\ (1(2)/(3)x)/(1(2)/(3)) = (13(1)/(3))/(1(2)/(3)) \\ \\ \boxed{x = 8, y = -1}](https://img.qammunity.org/2023/formulas/mathematics/college/47kty2x2bditrsiaap90xg4l6pzghstv9z.png)
_______________________________________________
![\displaystyle \left \{ {{y = -3x + 5} \atop {y = -8x + 25}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/pa0ldimbzexkq9vjtar1zogl2r3micwrwz.png)
{y = −3x + 5
{−⅜[y = −8x + 25]
![\displaystyle \left \{ {{y = -3x + 5} \atop {-(3)/(8)y = 3x - 9(3)/(8)}} \right. \\ \\ ((5)/(8)y)/((5)/(8)) = (-4(3)/(8))/((5)/(8)) \\ \\ \boxed{y = -7, x = 4}](https://img.qammunity.org/2023/formulas/mathematics/college/qhkauqx7d3z9wwcs73kbepe9zq9cqzg0sv.png)
------------------------------------------------------------------------------------------
![\displaystyle \left \{ {{y = -x + 1} \atop {y = 4x - 14}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/4rnbyu43cygp3md3obwydtx13psf62xvpn.png)
{y = −x + 1
{¼[y = 4x - 14]
![\displaystyle \left \{ {{y = -x + 1} \atop {(1)/(4)y = x - 3(1)/(2)}} \right. \\ \\ (1(1)/(4)y)/(1(1)/(4)) = (-2(1)/(2))/(1(1)/(4)) \\ \\ \boxed{y = -2, x = 3}](https://img.qammunity.org/2023/formulas/mathematics/college/onk7zzgx44m0rfcwsy5n0sn7n5zvwp54iz.png)
_______________________________________________
I am joyous to assist you at any time.